The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1103/physrevb.92.245412
|View full text |Cite
|
Sign up to set email alerts
|

Conductance, valley and spin polarizations, and tunneling magnetoresistance in ferromagnetic-normal-ferromagnetic junctions of silicene

Abstract: We investigate charge conductance and spin and valley polarization along with the tunnelling magneto-resistance (TMR) in silicene junctions composed of normal silicene and ferromagnetic silicene. We show distinct features of the conductances for parallel and anti-parallel spin configurations and the TMR, as the ferromagnetic−normal−ferromagnetic (FNF) junction is tuned by an external electric field. We analyse the behavior of the charge conductance and valley and spin polarizations in terms of the independent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Owing to size effect, electronic transport properties depend on the strip length and width [44,45]. According to typical normal-ferromagnetic-normal structure [46], we assume that the strip width is 40 nm and the length is 140 nm while the width of the ferromagnetic region is 20 nm. In this size, the piezoelectric potential is same order of magnitude with the energy intervals between subbands.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to size effect, electronic transport properties depend on the strip length and width [44,45]. According to typical normal-ferromagnetic-normal structure [46], we assume that the strip width is 40 nm and the length is 140 nm while the width of the ferromagnetic region is 20 nm. In this size, the piezoelectric potential is same order of magnitude with the energy intervals between subbands.…”
Section: Resultsmentioning
confidence: 99%
“…A ferromagnetic field with strength M is uniformly applied in the whole sample. From previous first-principles calculations, it is known that the low-energy electrons in heavy group-IV monolayers can be described by an effective Hamiltonian which reads [20][21][22][23], where λ (3.9 meV for silicene, 43 meV for germanene, 100 meV for stanene) represents the spin-orbit coupling, h = + -…”
Section: Realization Of the Valley-spin Seebeck Effectmentioning
confidence: 99%
“…To control the valley and spin in 2D Dirac materials, people usually adopt electric and optical methods to obtain valley-polarized or spin-polarized detectable effects [20][21][22][23][24][25][26][27][28], whereas only limited work has utilized the temperature difference to understand the valley Seebeck effect [29,30] or spin Seebeck effect [31][32][33][34], which can explore the possibility of directly converting heat into electrical power. Phenomenologically, the valley (spin) Seebeck effect indicates currents from two different valleys (spins) flowing in opposite directions.…”
Section: Introductionmentioning
confidence: 99%
“…This two-dimensional (2D) material has been grown experimentally by successful deposition of silicene sheet on silver substrate [9][10][11] . Also the interest in silicene soared due to the possibility of its various future applications ranging from spintronics [13][14][15][16][17] , valleytronics [18][19][20][21][22] to silicon based transistor 23 at room temperature. Very recently, it has been reported that low energy excitations in silicene follows relativistic Dirac equation akin to graphene 7,24 .…”
Section: Introductionmentioning
confidence: 99%